2013
DOI: 10.1002/cyto.a.22403
|View full text |Cite
|
Sign up to set email alerts
|

A method for evaluating the use of fluorescent dyes to track proliferation in cell lines by dye dilution

Abstract: Labeling nonquiescent cells with carboxyfluorescein succinimidyl ester (CFSE)-like dyes gives rise to a population width exceeding the threshold for resolving division peaks by flow cytometry. Width is a function of biological heterogeneity plus extrinsic and intrinsic error sources associated with the measurement process. Optimal cytometer performance minimizes extrinsic error, but reducing intrinsic error to the point of facilitating peak resolution requires careful fluorochrome selection and fluorescent cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 47 publications
3
62
0
Order By: Relevance
“…S1A-S1C). Moreover, we could not use cell sorting to reduce biologic heterogeneity without the possibility of biasing the cell population studied (10). As AML samples usually have a poor viability at thawing and at later points (see details of influence of cell viability in Supplementary Figs.…”
Section: Resultsmentioning
confidence: 99%
“…S1A-S1C). Moreover, we could not use cell sorting to reduce biologic heterogeneity without the possibility of biasing the cell population studied (10). As AML samples usually have a poor viability at thawing and at later points (see details of influence of cell viability in Supplementary Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Based on these criteria, we previously found that CellTrace Violet™ (CTV) was the favourable option for working with non-quiescent cells and that e-Flour Proliferation Dye 670™ (EPD) was the least favourable. We also found that certain cell lines were simply at the limit of this approach because the measurement errors associated with analysing such cells by flow cytometry meant that even sorting a narrowed input lead to spreading beyond the limits for peak resolution [20]. In this study, we have extended our appraisal to cover two lipophilic dyes PKH26™ and CellVue Claret™ (CVC) as well as a relatively new red excited version of CTV called CellTrace Far Red™ (CTFR).…”
Section: Introductionmentioning
confidence: 95%
“…When the dye labelled population of cells is sorted to narrow the input width and re-measured to determine the measurement error as a function of population re-spreading, the dye should make a minimal contribution to any measurement errors. Finally, once in culture it should be well retained and inherited in a symmetrically fashion across the plane of cytokinesis [20]. Based on these criteria, we previously found that CellTrace Violet™ (CTV) was the favourable option for working with non-quiescent cells and that e-Flour Proliferation Dye 670™ (EPD) was the least favourable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…S7) conforming that our GFP tag did not in any way inhibit the translocation function of NFAT in response to strong signals that bypass the TCR. We then labelled the GFP expressing cells with DiH-Rhod2, MitoDR and DCV to stain the nucleus in live cells with minimal effect on viability (Begum et al, 2013). We then activated these cells with 1 μg/ml CD3 in the presence of Ca 2+ and measured DiH-Rhod2 fluorescence within the MitoDRdefined cell area and correlated this with the degree of NFAT-GFP nuclear translocation for 20 min (Fig.…”
Section: Ifc Uniquely Allows For the Simultaneous Kinetic Measurementmentioning
confidence: 99%